PENGARUH KONFLIK, STRES KERJA, DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PT DUTA PLAST DI SUKOHARJO - Arif Nur Saputro; Amin Wahyudi; Erni Widajanti (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2019)
This study aims to examine the effect of work stress conflicts and organizational culture on employee performance. The first hypothesis examines whether conflicts have a positive and significant effect on employee performance. The second hypothesis examines whether job stress has a positive and significant effect on employee performance. The third hypothesis examines whether organizational culture has a positive and significant effect on employee performance. The population in this research is 475 employees at PT Duta Plast in Sukoharjo. This research is a census study using proportional random sampling technique. The sample used was 119 people by referring formula from arikunto because of the large population. Methods of data collection using questionnaires and documentation. Analyzer used in this research is multiple linear regression and absolute difference test. The results of the research instruments show that the overall variables of conflict, work stress, organizational culture and employee performance are valid and reliable. The results of the classical assumption test show that the free data multicollinearity, free autocorrelation, free heteroscedasticity and normal distributed data. The result of the research instrument test shows that work stress conflict, and organizational culture have a significant effect on the performance of PT Duta Plast in Sukoharjo.Keywords: Conflict, work stress, organizational culture, employee performance